2010
DOI: 10.2527/jas.2010-2907
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting beef cattle producer perspectives on feed efficiency1

Abstract: To establish the basis for implementation of a producer education program, a social assessment of the willingness and barriers to adoption of a measure of feed efficiency in beef cattle [residual feed intake (RFI)] was conducted. A 35-question mailed survey was sent to 1,888 producers acquired from the stratified random sample of the Idaho Cattle Association member list (n = 488), Red Angus Association of America member list (n = 2,208), and Red Angus Association of America bull buyer list (n = 5,325). The adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
1
Order By: Relevance
“…Wulfhorst et al (2010), in their social assessment of perception of producers about RFI in the United States, concluded that "the RFI concept is complex and not readily understood when fi rst encountered, even for trained scientists." Once the data are available, ratio traits can easily be calculated, but residual traits must be calculated by individuals familiar with least squares regression unless feed tables are used.…”
Section: Comparison Of Defi Nitions Of Feed Effi Ciency In Growing Anmentioning
confidence: 99%
“…Wulfhorst et al (2010), in their social assessment of perception of producers about RFI in the United States, concluded that "the RFI concept is complex and not readily understood when fi rst encountered, even for trained scientists." Once the data are available, ratio traits can easily be calculated, but residual traits must be calculated by individuals familiar with least squares regression unless feed tables are used.…”
Section: Comparison Of Defi Nitions Of Feed Effi Ciency In Growing Anmentioning
confidence: 99%
“…In a third situation, where no genetic evaluation is available to the producer, RFI can be used to rank animals for feed efficiency within population. It should also be taken into consideration when proposing RFI, RIG or residual intake and gain to producers as a selection criterion that it is a difficult concept to grasp (Wulfhorst et al ., 2010) and this may lower industry acceptance of residual feed efficiency measures. It is positive to note that RFI is favorably genetically correlated or not correlated with the majority of other production and carcass quality traits as previously discussed and selection for RFI will reduce GHG emissions in ruminants.…”
Section: Breeding For Low Rfi and Reduced Ch4 Emissionsmentioning
confidence: 99%
“…The lack of clear definition was suggested as one of the reasons for the low uptake of RFI breeding values in the beef industry (Wulfhorst et al, 2010). It is important for un-derstanding acceptance and encouraging wide adoption to carefully consider how to define and subsequently calculate the breeding value.…”
Section: Introductionmentioning
confidence: 99%